A study of prevalence of peripheral neuropathy in patients with impaired glucose tolerance - Gupta, Sumit; Sundaramurthy, Harsha; S. C., Nemichandra; Paneyala, Shasthara (International Journal of Research in Medical Sciences, 2022)
Background: It is estimated that about half of the diabetics develop diabetic peripheral neuropathy (DPN). Prediabetes is the precursor of type 2 diabetes and it is projected that by 2045 nearly 8.6% of the global adult population may be affected by prediabetes. Pre diabetics also shares the vascular complications of diabetes. Evaluation of impaired glucose tolerance (IGT) and its association with neuropathy is hence very essential. According to International Diabetes Federation, number of global impaired glucose regulation (IGR) patients will reach 471 million by 2035. It is imperative that management strategies aimed at timely diagnosis and prevention of these complications be framed. Methods: 30 patients with IGT were recruited from outpatient/inpatient department of JSS hospital who met the following WHO diagnostic criteria (HbA1C of 5.7-6.4%, fasting blood sugar of 100-125 mg/dl, oral glucose tolerance test (OGTT) 2-hour blood sugar of 140-199 mg/dl) were included in the study. All the patients underwent nerve conduction studies as per the established clinical practice and results were compared with the standard values of our laboratory. Results: 13 patients (43.33%) had neuropathy based on nerve conduction studies (NCS). Sensory neuropathy (53.85%) was most common followed by motor and mixed types with 3 patients each (23.08%). Conclusions: Prevalence of neuropathy was high in prediabetics. Small fibre involvement as manifested by sensory component was predominant in our study. Family history of diabetes was an important risk factor associated with higher neuropathy prevalence.